Reindeer shape soil methanogenic and methanotrophic communities in subarctic fen peatlands, with a minor impact on methane emissions : A field study - Laiho, Raija; Salovaara, Petri; Mäkiranta, Päivi; Peltoniemi, Krista; Penttilä, Timo; Rajala, Tuomas; Hultman, Jenni; Korkiakoski, Mika; Fritze, Hannu (Soil Biology and Biochemistry)
Laboratory and field studies with other grazer species suggest that reindeer (Rangifer tarandus L.) grazing on northern peatlands could shape the peat soil microbial communities and lead to higher ecosystem methane (CH4) emissions. We investigated this at two sedge fens in northern Finland, Lompolojänkkä and Halssiaapa, in experiments where reindeer grazing presence or absence was achieved with exclosure fences, and the effects of reindeer droppings were evaluated comparing dropping additions either on peat surface or trampled into the peat to controls with no droppings. Active soil methanogen and methanotroph communities were analyzed by metatranscriptomics. Soil CH4 fluxes were quantified with manual chambers and portable gas analyzer. Reindeer presence and dropping additions were both connected to differences in the soil communities as compared to controls (no presence or no droppings). The responses differed between the two fens. Activity of rumen microbes in peat could not be detected. Structural equation models indicated that the ecosystem CH4 flux in both fens depended on measurement year and sedge leaf area. At Halssiaapa trampled droppings, and at Lompolojänkkä both surface and trampled droppings reduced the sedge leaf area. While at Halssiaapa the dropping effect was not altogether statistically significant, in Lompolojänkkä surface droppings reduced the CH4 flux both directly and through the reduced leaf area. In conclusion, while both reindeer presence and dropping addition were diversely reflected in the active soil communities, reindeer effects on the CH4 flux were indirect and mediated via vegetation. The results contrast our earlier laboratory findings, and i) caution against liberal generalizations from lab studies to field conditions in peatlands, as well as ii) point to a need for rigorous multivariate analyses for deciphering the complex interactions governing the functions of these ecosystems. 2024